Efektifitas Pelayanan Gembala Sidang dalam Bimbingan Konseling Terhadap Kerohanian Warga Binaan Kristen di Lapas Klas II A Pontianak - Hermanto, Abang (Jurnal Kala Nea, 2020)
Abstract: The purpose of the study is to obtain a clear explanation of the condition of Christian Guided Residents in Class II A Laps in Pontianak. Furthermore, it becomes a reference for the Pastor in particular and the church in general to participate in improving the spiritual quality of Christian Guided Residents in Class II A Laps in Pontianak. This type of research is a qualitative research method with a phenomenological approach. The results of this study illustrate the experience of the Shepherd Session Church of the Indonesian Gospel Camp Area Pontianak. In this study researchers conducted several stages, namely: Rereading the results of in-depth interviews. Make verbatim transcripts carefully to analyze data in full from the results of the interview. Clarifying the data by taking verbatim transcripts to all participants. Analyze keywords by underlining or creating meaningful word codes. Analyze several of the same keywords to be organized into categories. Analyzing categories to create themes. The themes that have been arranged are analyzed whether answering the research objectives or by discussing with the supervisor. From the results of the questionnaire and interview questionnaire, two themes are identified, these themes are: First, Non-Intensive Counseling Guidance is Implemented. Second, Less Effective Counseling Guidance. Keywords: Effectiveness of Pastoral Service, Guidance for Spiritual Counseling Christian Guided Residents